PENGARUH MODEL PEMBELAJARAN TIME TOKEN TERHADAP HASIL BELAJAR PPKN PADA SISWA KELAS V SDN BIRINGKALORO KABUPATEN GOWA - Amsis, Nurcholifha; Suardi; Aba, Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Time Token learning model on the Civics (PPKn) learning outcomes of fifth-grade students at SDN Biringkaloro, Gowa Regency. The study employed a quantitative approach with a pre-experimental One Group Pretest–Posttest design. The sample consisted of 24 students selected using a saturated sampling technique. Data were collected through tests, observation, and documentation, and analyzed using descriptive and inferential statistics (normality test and paired sample t-test with SPSS). The results showed an increase in the average score from 72.00 (pretest) to 92.00 (posttest), and learning mastery improved from 46% to 100%. The implementation of the learning model was categorized as very high (91%). The hypothesis test yielded a significance value of 0.000 (< 0.05), indicating that the Time Token learning model has a significant and positive effect on students’ Civics learning outcomes and enhances their active participation.